New records of marine invertebrates from Ascencion Island (Central Atlantic) - Brown, Judith (2016)
The sea anemone Telmatactis forskalii, the zoanthid Isaurus tuberculatus, the nemertine Baseodiscus delineatus, the echinoderms Ophiocoma wendtii and Mithrodia clavigera, the molluscs Colubraria canariensis, Glyphepithema turtoni, Tonna pennata, Trivia candidula, Melanella eburnea, Melanella n.sp., Echineulima leucophaes, Stylocheilus striatus, Limaria hians, Pteria hirundo and Callistoctopus macropus, and the crustaceans Tetraclitella sp., Oxynaspis celata, Thor amboinensis and Parribacus antarcticus are recorded from Ascension Island for the first time. A new depth record is given for the sea anemone Telmatactis cricoides. An undescribed shrimp species of the genus Lysmata and the shrimp Lysmata moorei were observed to clean fish at night.